Keanekaragaman Arthropoda dan Penyakit Tanaman Padi di Desa Kusambi Hilir Kecamatan Lampihong - Atiatul Jannah; Yusriadi Marsuni; Samharinto Soedijo (www.ulm.ac.id, 2023)
The purpose of this study was to identify the types of arthropods and diseases in rice plants, especially those in Kusambi Hilir Village, Lampihong District. The method used is a survey method by taking arthropod samples, using insect nets and light traps, observing symptoms of rice plant diseases. The results of the study found that the number of arthropods in paddy fields near the rubber plantations was 219 consisting of 162 individuals (73.97%) pests, 43 individuals (19.63%) predators, 6 individuals (2.73%) parasitoids and 8 individuals ( 3.65%) other arthropods. The number of arthropods in paddy fields near the main road was 159 individuals consisting of 100 individuals (62.89%) pests, 45 individuals (28.30%) predators and 14 individuals (8.81%) parasitoids. The dominant arthropods and diseases in rice are Scirpophaga incertulas Walker and bacterial leaf blight. The diversity index of arthropods is categorized as low because a diversity index of 2.577 is obtained in paddy fields near the main road and (H') is 2.348 in paddy fields near rubber plantations.